Integrasi Nilai Moderasi Beragama dalam Mata Kuliah Perbandingan Pendidikan Islam di Perguruan Tinggi - Selvi Pransiska (Lembaga Yasin AlSys, 2026)
The prevalence of religious understanding that tends to be exclusive in the campus environment underscores the importance of strengthening religious moderation through structured and sustainable academic pathways. This study aims to examine the concept of integrating religious moderation values into the Islamic Education Comparison course, analyze its implementation in the learning process, and formulate an integrative model that is applicable and replicable in Islamic higher education. This study employed a qualitative approach with a case study design in the Islamic Religious Education Study Program at IAIN Curup, with fourth-semester students selected purposively as the research subjects. Data were collected through participatory observation, in-depth interviews, and curriculum documentation, and were then analyzed using an interactive model that included data condensation, data display, and iterative conclusion drawing. The results revealed three main findings. First, the values of religious moderation, such as tawassuth, tawazun, tasamuh, and i'tidal, have been implicitly embedded in the curriculum structure, but have not yet been standardized as measurable learning outcomes. Second, the implementation of religious moderation took place organically through a dialogic-comparative approach that was proven to transform students’ religious orientation from exclusive to inclusive. Third, this study produced the KTIM Model (Comparative-Transformative-Inclusive-Moderate) as a structured and applicable integration framework. These findings contribute to the development of a moderation-based Islamic education curriculum that is responsive to the needs of Indonesia’s plural society and underscore the importance of integrating the values of religious moderation more systematically into learning in Islamic higher education.